Overview of primary adult retroperitoneal tumours. Issue 9 (September 2020) - Improta, Luca; Tzanis, Dimitri; Bouhadiba, Toufik; Abdelhafidh, Khoubeyb; Bonvalot, Sylvie
Abstract: In front of a primary retroperitoneal tumour, it is necessary to have in mind all possible diagnoses in order to specify the diagnostic strategy and the treatment. According to the World Health Organization (WHO) classification of tumours, mesenchymal benign and malignant tumours (including sarcomas and, currently, neurogenic tumours), parasympathetic tumours, extragonadal germ cell tumours, and lymphoid tumours have been identified. By definition, primary retroperitoneal tumours start independently from the retroperitoneal organs. Secondary lesions, carcinoma metastasis, and adenopathy are excluded from this definition, but they can also develop in the retroperitoneal space and lead to misdiagnoses. In the absence of positive tumour markers or an evocative biology, percutaneous biopsy is necessary. Pathological diagnosis is necessary to decide whether surgery must be done, its timing among the other treatments, and its extension. This paper summarizes all the diagnostic possibilities. Highlights: - Retro- and infraperitoneal tumours: Percutaneous biopsy is the standard of care. In fact, the indications for and extent of surgery depends on the diagnosis. - Both the early complication rate and the incidence of needle tract seeding of per cutaneous biopsy of an RP mass are very low. - The well-differentiated components of liposarcomas are often underestimated, leading to incomplete surgery, which definitely worsens prognosis. - The surgical standard of care for sarcoma is a complete, non-fragmented, en bloc resection with clear margins on the larger surface. Typical resection is a compartmental surgery, with en bloc resection of the kidney, colon, and psoas fascia. Adjustments are made according to the histological subtype. - Sarcoma surgery must be performed in a referral sarcoma centre.